Secular education Why and for what? - Morales García, Juan Javier (2018)
What is presented below is part of an investigation entitled “The potential of secular education in primary school” (2010, ISCEEM, Toluca, Mexico) based on the theory of the new cultural paradigm of Alain Touraine, as well as contributions of the main representatives of secularism such as Henri Peña, Jean Bauberot and Roberto Blancarte. For this article some reflections are presented regarding the theme of secularism in Mexican public education, its meaning, its interpretations, the cultural battles around it and, above all, its potentialities in citizen education in basic education. Its objective is to address the five most relevant aspects that secular training can provide and that, by far, exceed the benefits that any clericalism could grant in public education. It is concluded that said secularism promotes equality and the common good that are also the basis of democracy; In addition, promoting freedom of conscience enables agents to make decisions based on criticism and reflection, essential for democracy.